Clinical outcome of PSMA-guided radiotherapy for patients with oligorecurrent prostate cancer - Körber, Stefan A.; Sprute, Katharina; Kratochwil, Clemens; Winter, Erik; Häfner, Matthias; Katayama, Sonja; Schlampp, Ingmar; Herfarth, Klaus; Kopka, Klaus; Afshar-Oromieh, Ali; Zschäbitz, Stefanie; Holland-Letz, Tim; et al. (European journal of nuclear medicine and molecular imaging, 2021)
First-line treatment of patients with recurrent, metastatic prostate cancer involves hormone therapy with or without additional systemic therapies. Prostate-specific membrane antigen (PSMA) positron emission tomography (PET)/computed tomography (CT) allows the detection of oligometastatic disease that may be amenable to image-guided radiotherapy. The current study classifies the type and localization of metastases and the clinical outcome of PSMA-PET/CT-guided radiotherapy to selected metastases.